Brain-blood ratio of morphine in heroin and morphine autopsy cases. (August 2019) - Nedahl, Michael; Johansen, Sys Stybe; Linnet, Kristian
Highlights: Blood and brain concentrations of morphine from heroin and morphine autopsy cases. Evaluation of the brain-blood ratio from heroin cases in contrast to morphine cases. Blood and brain concentrations of morphine-6-glucuronide and 6-acetyl-morphine. Evaluation of noscapine and papaverine as markers of illegal heroin use. Abstract: Brain tissue is a useful supplement to blood in postmortem investigations, but reference concentrations are scarce for many opioids. Heroin cases may be difficult to distinguish from morphine cases as heroin and its metabolites are rapidly degraded. We present concentrations from brain and blood and brain–blood ratios of 98 cases where morphine was quantified. These cases were grouped according to the cause of death: A: The compound was solely assumed to have caused a fatal intoxication. B: The compound presumably contributed to a fatal outcome in combination with other drugs, alcohol or disease. C: The compound was not regarded to be related to the cause of death. The cases were further classified as heroin cases if 6-acetyl-morphine or noscapine were detected. The analyses were carried out using solid-phase extraction or protein precipitation followed by ultra high-performance liquid chromatography coupled to mass spectrometry. The average brain-blood ratios of morphine were 1.2 and 1.8 for 69 morphine and 29 heroin cases, respectively. Differences in the brain-blood ratios were found for cases where heroin and morphine were involved in the cause of death, either in combination or on its own (P < 0.001 and P = 0.004, respectively). However, the overlap between morphine and heroin cases precludes the use of the brain-blood ratio to distinguish heroin from morphine intake. Morphine-6-glucuronide and 6-acetyl-morphine were quantified in brain and blood in a subset of the samples, yielding median brain-blood ratios of 5.1 and 8.3, respectively. The brain concentrations may aid the toxicological investigation in cases where heroin or morphine intoxications are suspected, but blood is not available.